(t+5)+3=12

Simple and best practice solution for (t+5)+3=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (t+5)+3=12 equation:


Simplifying
(t + 5) + 3 = 12

Reorder the terms:
(5 + t) + 3 = 12

Remove parenthesis around (5 + t)
5 + t + 3 = 12

Reorder the terms:
5 + 3 + t = 12

Combine like terms: 5 + 3 = 8
8 + t = 12

Solving
8 + t = 12

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + t = 12 + -8

Combine like terms: 8 + -8 = 0
0 + t = 12 + -8
t = 12 + -8

Combine like terms: 12 + -8 = 4
t = 4

Simplifying
t = 4

See similar equations:

| 30=-5(6n+7) | | -2(t+7)-(t+5)=5 | | 4t+12-10= | | y=20+150 | | 36p-49p^3=0 | | 11m^2+3m=0 | | (X-2)(X+1)-4=0 | | 8x-10y=30 | | 4x-7=-2x+9 | | -3=-31+16.666 | | 0.10(m-100)+15+20=0.05m+40 | | 7t=6 | | 2x-19+3x+6+2x-10=180 | | 17k^2+119k=0 | | 9a-4=14 | | 4x=5y+6 | | A/6=-18 | | -3+9=-21 | | 2a+x=7 | | 3x+(-15+3x)=21 | | 8x-52=x | | 11x-9=8x+6 | | 9g^2+g=0 | | -7/3(y-12)-1/9y | | C-7.2=12 | | 3x^2+36x-8=0 | | 3x^2=19x+14 | | 13=-2+c | | y=ln(x^4+e^2x) | | 4*sin*2x-1=-5 | | -4b^2+81=0 | | 3(20+h)=1 |

Equations solver categories